Factors Influencing and Information Technology Interventions for Nurse Compliance on Patient Safety: A Systematic Review - Setiawati, Deni; Setyowati, Setyowati; Hariyati, Rr. Tutik Sri; Mediati, Ati Surya; Hidayanto, Achmad Nizar; Tuba, Syahrul (Poltekkes Kemenkes Palu, 2024)
Patient safety is a critical global issue, prevalent in many countries. This research aims to review publications and literature regarding the factors and interventions that aid in nurse compliance with patient safety measures. Due to limited published studies on this topic, we conducted a systematic review to identify these factors and interventions based on existing literature. We searched databases including Scopus, Science Direct, PubMed, and ClinicalKey Nursing, using specific keywords, filtering 1918 articles down to 22 articles for analysis. The study reveals that nurse implementation of patient safety is influenced by organizational culture and leadership, resource accessibility, physical facilities, communication and collaboration, workload and job satisfaction, nurses' knowledge and skills, demographic factors, and their attitudes and perceptions. Interventions for enhancing nurse compliance in patient safety include providing training and education through technological approaches, and health service delivery via information technology systems. This review offers insights into resolving nurse compliance issues in patient safety, highlighting the importance of not only individual nurses but also hospital management and the healthcare delivery system. Effective management strategies to increase nurse compliance in patient safety should involve hospital authorities and improvements in the nursing service system.